ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERNAL TERHADAP PEMBERIAN KREDIT (STUDI KASUS PADA PT. BANK KARTADHANI MULYA KABUPATEN SUKOHARJO) - Heni Ramita Sari; Setyani Sri Haryanti (STIE AUB Surakarta, 2019)
Internal control is an organization planning and method which is used to keep or protect assets, to create accurate and trusted information, to fix efficiency, and to drive the management policy to be obeyed. The purposes of this research are to know the implementation of internal control system towards credit loan at PT. BPR Karthadhani Mulya Kabupaten Sukoharjo. This research uses case study at PT. BPR Kartadhani Mulya in Sukoharjo. Technique of collecting data uses interview, observation, and documentation. While technique of analyzing data uses control testing by using stop-or-go sampling method. The result of analysis data can be summarized that internal control system towards credit loan which is done by PT. BPR Kartadhani Mulya Kabupaten Sukoharjo has met the requirement of internal control system according to COSO (Committee of Sponsoring Organization). It consists of control environment, risk assessment, controlling activities, information and communication, and controlling.